SURVEY EMPIRIS MUTU LAYANAN PEMBELAJARAN MAHASISWA PPG UNIVERSITAS WIDYA DHARMA KLATEN - Tukiyo, Tukiyo; Purwo Haryono; Tasari, Tasari; Hersulastuti, Hersulastuti; Dandang Setyawanti; Nugrahani, Cahaya; Jarot Prasetyo (FAKULTAS EKONOMI UNWIDHA KLATEN, 2025)
The purpose of this PPG Study Program research scheme is to analyze the satisfaction index model of Widya Dharma University Teacher Professional Program students from the quality of academic and non-academic learning services through analysis of the satisfaction value of each element. The research method used is quantitative research. Respondents in the research were 200 students. The sampling technique was carried out by purposive sampling. Quantitative tests in research in the form of primary data description tests and statistical value descriptions of each element. The results of this research obtained values that have the highest points and values that still have shortcomings of each element of academic learning quality, non-academic, satisfaction and loyalty.